2016
DOI: 10.1167/16.3.33
|View full text |Cite
|
Sign up to set email alerts
|

Action recognition in the visual periphery

Abstract: Recognizing whether the gestures of somebody mean a greeting or a threat is crucial for social interactions. In real life, action recognition occurs over the entire visual field. In contrast, much of the previous research on action recognition has primarily focused on central vision. Here our goal is to examine what can be perceived about an action outside of foveal vision. Specifically, we probed the valence as well as first level and second level recognition of social actions (handshake, hugging, waving, pun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
(42 reference statements)
2
9
0
Order By: Relevance
“…Similar adaptation aftereffects in central vision and at 40° eccentricity indicate that action recognition mechanisms that are susceptible to adaptation can discriminate actions even in the far periphery. These results are in line with other research that suggests that participants have little difficulty in recognizing moving actions in the visual periphery up to 45° eccentricity ( Fademrecht et al., 2016 ).…”
Section: Methodssupporting
confidence: 93%
See 3 more Smart Citations
“…Similar adaptation aftereffects in central vision and at 40° eccentricity indicate that action recognition mechanisms that are susceptible to adaptation can discriminate actions even in the far periphery. These results are in line with other research that suggests that participants have little difficulty in recognizing moving actions in the visual periphery up to 45° eccentricity ( Fademrecht et al., 2016 ).…”
Section: Methodssupporting
confidence: 93%
“…These results corroborate what we have observed in Experiment 2 with an adaptation paradigm. Moreover, these findings also agree with a previous study that had showed that action recognition is possible in far periphery up to 60° but tends to decrease for eccentricities larger than 45° ( Fademrecht et al., 2016 ). Hence, these results suggest that the presence of a crowd reduces the accuracy of action recognition in the periphery if the crowd is executing similar actions to that of the target actor, but this effect is not observed in central vision.…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…Work by Ludvigh and Miller [16] has already described the ability of the eyes to resolve stimuli that move relative to an observer as "dynamic visual acuity". It is interesting to note that most methods that have been used to investigate specific perceptual and attentional capabilities or processes of the cognitive system, have focused on interactions with static stimuli; and that the various studies that have compared static and dynamic stimuli suggest that dynamic events show an overall higher sensitivity over the visual field than static events (see e.g., [17]). However, it has also been claimed that attending to dynamic stimuli comes at a higher cost than static stimuli [18].…”
Section: Introductionmentioning
confidence: 99%